Supply Chain Resilience: Warehousing Role and Regionalization Effect During COIVD-19 - Mohammed Y Al Rebh; Ali K Al Fardan (ExcelingTech, 2022)
This paper discusses supply chain resilience, how warehousing and regionalization plays a role during unforeseen disruptions. The paper includes a literature review that covers business continuity, a dive down into supply chain resilience and its strategies, as well as brief sections for the inventory management and supplier development roles. In addition, a study has been conducted that allowed us to derive key lessons learned from this case analysis where supply chain resilience strategies have had a major impact on determining the various supply chain parts roles and weight during the uncertainties brought by COVID-19 Pandemic and Global Financial Crisis. The findings indicated that warehousing and regionalization which are contradicting with JIT and globalization concepts contributed in the greater supply chain resilience.